FEAR, RELIGIOSITY AND POLICY: WITH REGARD TO THE 1812 EARTHQUAKE. - Rodríguez, Pablo (Revista de Historia Social y de las Mentalidades, 2011)
This article analyzes the impact that had the earthquake of the 26 of March of 1812 in the policy and Venezuelan society. It describes the destruction that produced in the cities. But, specially it is concentrated in the study of the fear that generated in the population and the way as it were manipulated in favor of one political position. The article concludes, that this earthquake was an important cause in the fall of the first established republican government in Venezuela.